IMPROVING THE METHODOLOGY FOR OPTIMIZING A HEALTHY LIFESTYLE OF STUDENTS BASED ON MODERN HEALTHY BREATHING EXERCISES TECHNOLOGY DURING THE LESSON. (Universal International Scientific Journal, 2026)
In this article, scientific research was conducted on the indicators of physical development of students of the Andijan State Pedagogical Institute to stimulate a healthy lifestyle and participation in the lesson. During the lesson, we conducted modern health-improving breathing techniques, and according to the initial part of the analysis, it was found that they do not lead a healthy lifestyle, and fatigue, irritability and other problems are observed during the lesson. According to the final results, we can see that the “square breathing” technology and “triangle breathing” methods used by us helped them to concentrate during the lesson, reduce activity, physical fatigue, increase interest in the lesson, and improve their mental state.
Keywords: : psycho-emotional, square-breath, technology, triangular breath, moral, functional, activity.